Greenwashing accusation score : a mensurement procedure - FREITAS NETTO, Sebastião Vieira de (2019)
Environmental issues are a major concern of stakeholders and of the Society as a whole. The problem is getting worse and consumers have come to value eco-innovative products that have less environmental impact. Faced with this demand, organizations around the world began to develop green products and apply green marketing strategies to gain competitiveness and differentiation. However, many companies intentionally or not, perform greenwashing, which misleads consumers to perceive higher social and/or environmental performance of a product/service and/or company, which may influence their decisions. Given this context, the general objective of this research is to analyze the phenomenon of greenwashing through a model, proposed to measure the phenomenon in organizations. The specific objectives of the research are: to identify definitions and concepts related to the phenomenon of greenwashing; identify characteristics and typologies related to the phenomenon of greenwashing; propose a model to measure the phenomenon of greenwashing; and apply the model to organizations and evaluate their results. The research has an exploratory and prescriptive characterization, through a quantitative approach. Applying a systematic literature review we identified the main dimensions and typologies of greenwashing, which were used for the development of the model called Greenwashing Accusation Score. The dimensions were called firm-level claim, firm-level executional, product-level claim and product-level executional, and a framework was developed. The proposed tool was applied in two multinational companies where the dimensions of analysis that obtained the highest score, firm-level executive and product-level greenwashing were highlighted. Which may indicate a greater application of elements called executionals rather than firm-level and product-level claim. The work has as limitation an single-person decision process, as a suggestion for future work, the model can be applied by a committee of experts by segment.